#### Answer

(1,4)

#### Work Step by Step

Multiply the first equation by 2. Add the equations to eliminate q.
$3p+q\ \ =\ \ 7\ \ \ \ $ multiply by 2 $\ \ \ \ 6p+2q=\ 14$
$2p-2q=-6\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \underline{2p-2q=-6}$
$\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ 8p\ \ \ \ \ \ \ \ \ =\ \ 8$
Solve for p.
$8p=8$
$8p\div8=8\div8$
$p=1$
Substitute 1 for p in either equation.
$3p+q=7$
$3(1)+q=7$
$3+q-3=7-3$
$q=4$